2022
DOI: 10.18203/2394-6040.ijcmph20221772
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of natural breastfeeding milk among mothers and the importance of colostrum within the first hour of birth in India

Abstract: Children should not suffer from the lack of adequate knowledge or ignorance from their parents. Breastfeeding colostrum is extremely useful for the immunity and growth of the newborn, as it is having been documented to improve neonatal survival, and protective against the infection specific mortality among newborn and mothers. The secondary data presented in this paper was abstracted from well-known search engines performed in March 2022. Search engines like Pubmed and Google scholar. In Pubmed 8 articles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Similarly, a high degree of awareness of exclusive breastfeeding by nursing mothers was also found in a prior study by Piro and Ahmed, as well as in Akinola et al study on awareness and importance of colostrum among nursing mothers. 17,18 The result of this survey showed that 64.4% of respondents have good knowledge about exclusive breastfeeding. In accordance to this study, a study carried out among mothers in Saudi Arabia showed that 65.7% respondents also had good knowledge on exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, a high degree of awareness of exclusive breastfeeding by nursing mothers was also found in a prior study by Piro and Ahmed, as well as in Akinola et al study on awareness and importance of colostrum among nursing mothers. 17,18 The result of this survey showed that 64.4% of respondents have good knowledge about exclusive breastfeeding. In accordance to this study, a study carried out among mothers in Saudi Arabia showed that 65.7% respondents also had good knowledge on exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 87%